2020
DOI: 10.5751/es-11464-250205
|View full text |Cite
|
Sign up to set email alerts
|

Multiattribute decision making for the assessment of disaster resilience in the Three Gorges Reservoir Area

Abstract: Disaster resilience assessments are critical to both urban and rural development, especially in disaster-prone regions. The Three Gorges Reservoir Area is a typical disaster-prone area, but there is a lack of research on disaster resilience in this area. We proposed a set of indicators and methodologies as a development of a comprehensive disaster resilience evaluation index system that encompasses societal, economic, natural environment, and infrastructure perspectives. Then an integrated approach, which comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…According to the previous review of existing resilience assessment methods, most conventional resilience assessment methods are based on subsystem attributes, subjective understanding of resilience, or single events -an evaluation system is formed by selecting indicators and factors that can describe the state of resilience from natural, economic, social, and cultural perspectives (Brown et al, 2018;Yang et al, 2020), or from different management stages, such as prevention, response, recovery, and adaptation (Ouyang et al, 2012;Zhang et al, 2021). As discussed in the introduction, many of these approaches do not always support cross-region comparison of resilience or assessment of resilience building practices.…”
Section: Features Of the Disaster-damage-based Resilience Assessment ...mentioning
confidence: 99%
“…According to the previous review of existing resilience assessment methods, most conventional resilience assessment methods are based on subsystem attributes, subjective understanding of resilience, or single events -an evaluation system is formed by selecting indicators and factors that can describe the state of resilience from natural, economic, social, and cultural perspectives (Brown et al, 2018;Yang et al, 2020), or from different management stages, such as prevention, response, recovery, and adaptation (Ouyang et al, 2012;Zhang et al, 2021). As discussed in the introduction, many of these approaches do not always support cross-region comparison of resilience or assessment of resilience building practices.…”
Section: Features Of the Disaster-damage-based Resilience Assessment ...mentioning
confidence: 99%
“…Generally, risk perception refers to the subjective feelings formed based on emotional fluctuations and an understanding of risk events, which affect risk‐coping behavior. In other words, risk perception varies with an individual's psychological status, experience, and knowledge structure, which indicates that there may be systematic bias and other cognitive errors in risk judgment (Yang, Guo, et al, 2020). During the investigation, we found that migrating farmers tend to ignore low‐probability and high‐impact geo‐hazards or underestimate the possibility of their families becoming disaster victims.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…China is one of the countries with the most severe geo‐hazards and the most threatened population in the world, and many high‐risk geo‐hazard points are widely distributed (Peng et al, 2020; Yang, Guo, et al, 2020). In recent years, with the implementation of various disaster reduction measures, the losses caused by geo‐hazards have been on the decline.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the impact of infrastructure on UR tends to increase when subjected to external shocks (Wang et al, 2018). In addition, in the water resources resilience, the explanatory power of residents' water-saving efficiency, sewage and wastewater treatment on UR increases year by year, which indicates that they have a crucial impact on improving the risk resistance of cities (Matthews et al, 2016;Rushforth et al, 2020;Yang et al, 2020). However, due to the large population and intensive resource consumption, the city is facing difficulties such as the lack of balance both supply and demand of water resources and the finite bearing capacity of water environment, which weakens the city' power when facing external shocks (Zhu and Chang, 2020).…”
Section: Fig 8 Spatial Differentiation Of Ur Along the Yreb's Lower Reachesmentioning
confidence: 99%